Distinct Effects of Ibrutinib and Acalabrutinib on Mouse Atrial and Sinoatrial Node Electrophysiology and Arrhythmogenesis - Jari M. Tuomi (Wiley, 2021)
Background Ibrutinib and acalabrutinib are Bruton tyrosine kinase inhibitors used in the treatment of B‐cell lymphoproliferative disorders. Ibrutinib is associated with new‐onset atrial fibrillation. Cases of sinus bradycardia and sinus arrest have also been reported following ibrutinib treatment. Conversely, acalabrutinib is less arrhythmogenic. The basis for these different effects is unclear. Methods and Results The effects of ibrutinib and acalabrutinib on atrial electrophysiology were investigated in anesthetized mice using intracardiac electrophysiology, in isolated atrial preparations using high‐resolution optical mapping, and in isolated atrial and sinoatrial node (SAN) myocytes using patch‐clamping. Acute delivery of acalabrutinib did not affect atrial fibrillation susceptibility or other measures of atrial electrophysiology in mice in vivo. Optical mapping demonstrates that ibrutinib dose‐dependently impaired atrial and SAN conduction and slowed beating rate. Acalabrutinib had no effect on atrial and SAN conduction or beating rate. In isolated atrial myocytes, ibrutinib reduced action potential upstroke velocity and Na+ current. In contrast, acalabrutinib had no effects on atrial myocyte upstroke velocity or Na+ current. Both drugs increased action potential duration, but these effects were smaller for acalabrutinib compared with ibrutinib and occurred by different mechanisms. In SAN myocytes, ibrutinib impaired spontaneous action potential firing by inhibiting the delayed rectifier K+ current, while acalabrutinib had no effects on SAN myocyte action potential firing. Conclusions Ibrutinib and acalabrutinib have distinct effects on atrial electrophysiology and ion channel function that provide insight into the basis for increased atrial fibrillation susceptibility and SAN dysfunction with ibrutinib, but not with acalabrutinib.